The Alzheimer's prevention program : keep your brain healthy for the rest of your life - Small, Gary, 1951- (Workman Pub. Co., 2011)
"The only "cure" for Alzheimer's is prevention, and The Alzheimer's Prevention Program shows the reader how to take control. The program begins with an assessment test checking everything from recall to physical balance. Then, with a baseline established, it introduces the 7-Day jumpstart program - just seven days to begin to improve everything: memory training 101, including the author's easy-to-use "Look, Snap, Connect" memory technique. Daily mental workouts to sharpen your brain: wordplay, letter scrambles, 3-D drawings, tricky equations, logic challenges, and number sequences. Healthy brain nutrition, filled with antioxidants - berries, avocados, raw vegetables; omega-3 rich, anti-inflammatory food choices, including fish, whole grains, legumes; and the memory-boosting spices most often found in Indian curries. Stress-reduction strategies to fortify neurons. Best aerobic and strength exercises"--